Non-linear association between dietary fiber intake and cognitive function mediated by vitamin E: a cross-sectional study in older adults - He, Qianyi; An, Lucy; Yue, Yue; Cui, Can; Wang, Chongjian; Xu, Hong; Guo, Yunfei; Zhao, Xinyu (Frontiers in Nutrition, 2025)
BackgroundEmerging evidence suggests dietary fiber may prevent cognitive decline, but its dose-response relationship and underlying mechanisms remain unclear. This study investigates the non-linear association between dietary fiber intake and cognitive function in older adults and explores the mediating role of vitamin E.MethodsThis cross-sectional analysis of nationally representative National Health and Nutrition Examination Survey (NHANES) Data from 2011 to 2014 included 2,713 adults aged ≥60 years. Dietary fiber intake was assessed using two 24-h dietary recalls. Cognitive function was evaluated using a comprehensive battery comprising three standardized assessments: the Digit Symbol Substitution Test (DSST) to measure processing speed, the Animal Fluency Test (AFT) to assess executive function, and a Consortium to Establish a Registry for Alzheimer's Disease (CERAD) subtest to evaluate memory performance. Composite z-scores were calculated for each individual test and combined to generate a global cognition composite score. Generalized additive models (GAM) were applied to model non-linear relationships, and threshold effects were evaluated using two-piece-wise linear regression. Mediation analysis quantified the mediating role of vitamin E in the dietary fiber-cognitive function association, with effects assessed via the non-parametric percentile bootstrap method. Subgroup-specific sensitivity analyses demonstrated consistent findings.ResultsA J-shaped relationship between cognitive function and dietary fiber intake was identified using a two-piece-wise linear regression model. DSST scores reached a plateau at 29.65 g/day of fiber intake (likelihood ratio test P < 0.001), while composite z-scores reached a plateau at 22.65 g/day (likelihood ratio test P = 0.018). Below the inflection point, dietary fiber intake demonstrated a positive association with DSST scores (β: 0.18, 95% CI: 0.01–0.26, P < 0.0001), whereas above this threshold, the relationship became negative (β: −0.15, 95% CI: −0.29 to −0.02, P = 0.0265). Similarly, for composite z-scores, a positive association was observed below the inflection point (β: 0.01, 95% CI: 0.00–0.01, P = 0.0004), while the relationship appeared to saturate above this threshold (β: −0.00, 95% CI: −0.01–0.00, P = 0.9043). Mediation analysis revealed that vitamin E intake significantly mediated 85.0% (P < 0.0001) of the association between dietary fiber intake and composite z-scores, and 86.8% (P < 0.0001) of the association between dietary fiber intake and DSST scores.ConclusionModerate dietary fiber intake is associated with optimal cognitive performance, largely mediated by vitamin E.